Karakterisasi Sumber Cahaya Menggunakan Spektrofotometer Vis-Nir untuk Optimasi Optical Non-Contact Speedometer - Johan Iskandar; Yunita Rahma; Sindy Andiani (Jurnal Ilmu Komputer, 2021)
Characterization the light source has been carried out using a Vis-Nir spectrophotometer with the Ocean Optics DTmini-2 model. The purpose of this characteristic is to obtain the optimum wavelength as a light source in making a digital optical non-contact speedometer model. There are 5 light sources tested, namely blue, green, yellow, red and white light. From the characterization results, the wavelengths were blue (450 nm), green (540 nm), yellow (570 nm), red (640 nm) and white (550 nm). In making the digital optical non-contact speedometer model, a photodiode sensor is used which has an absorbance peak point at 479 nm, 680, and 900 nm. The working principle of the prototype is to detect changes in light intensity as a result of the reflectance by the wheel. The sensor reads every color changes on the wheel and the results will be sent to the microcontroller for further processing. The results obtained are that the red LED is excellent to this prototype because it has the highest ADC value compared to other light sources tested. This is consistent with the results of the sensor spectrophotometer characterization.